Dual RNA-seq study of the dynamics of coding and non-coding RNA expression during Clostridioides difficile infection in a mouse model - Victor Kreis; Claire Toffano-Nioche; Cécile Denève-Larrazet; Jean-Christophe Marvaud; Julian R. Garneau; Florent Dumont; Erwin L. van Dijk; Yan Jaszczyszyn; Anaïs Boutserin; Francesca D'Angelo; Daniel Gautheret; Imad Kansau; et al. (mSystems)
ABSTRACT Clostridioides difficile is the leading cause of healthcare-associated diarrhea in industrialized countries. Many questions remain to be answered about the mechanisms governing its interaction with the host during infection. Non-coding RNAs (ncRNAs) contribute to shape virulence in many pathogens and modulate host responses; however, their role in C. difficile infection (CDI) has not been explored. To better understand the dynamics of ncRNA expression contributing to C. difficile infectious cycle and host response, we used a dual RNA-seq approach in a conventional murine model. From the pathogen side, this transcriptomic analysis revealed the upregulation of virulence factors, metabolism, and sporulation genes, as well as the identification of 61 ncRNAs differentially expressed during infection that correlated with the analysis of available raw RNA-seq data sets from two independent studies. From these data, we identified 118 potential new transcripts in C. difficile, including 106 new ncRNA genes. From the host side, we observed the induction of several pro-inflammatory pathways, and among the 185 differentially expressed ncRNAs, the overexpression of microRNAs (miRNAs) previously associated to inflammatory responses or unknown long ncRNAs and miRNAs. A particular host gene expression profile could be associated to the symptomatic infection. In accordance, the metatranscriptomic analysis revealed specific microbiota changes accompanying CDI and specific species associated with symptomatic infection in mice. This first adaptation of in vivo dual RNA-seq to C. difficile contributes to unravelling the regulatory networks involved in C. difficile infectious cycle and host response and provides valuable resources for further studies of RNA-based mechanisms during CDI.IMPORTANCEClostridioides difficile is a major cause of nosocomial infections associated with antibiotic therapy classified as an urgent antibiotic resistance threat. This pathogen interacts with host and gut microbial communities during infection, but the mechanisms of these interactions remain largely to be uncovered. Noncoding RNAs contribute to bacterial virulence and host responses, but their expression has not been explored during C. difficile infection. We took advantage of the conventional mouse model of C. difficile infection to look simultaneously to the dynamics of gene expression in pathogen, its host, and gut microbiota composition, providing valuable resources for future studies. We identified a number of ncRNAs that could mediate the adaptation of C. difficile inside the host and the crosstalk with the host immune response. Promising inflammation markers and potential therapeutic targets emerged from this work open new directions for RNA-based and microbiota-modulatory strategies to improve the efficiency of C. difficile infection treatments.